The burden of preventable hospitalizations before and after implementation of the health transformation plan in a hospital in west of Iran - Piroozi, Bakhtiar (Prim Health Care Res Dev, 2019)
BACKGROUND: Increased number of preventable hospitalizations (PHs) for ambulatory care sensitive conditions (ACSCs) represents less efficiency and low access to outpatient and primary health care, leading to waste of health system resources. AIM: The purpose of this study is to assess the quality of outpatient and primary health care using the rate of PHs for ACSCs and to estimate the economic burden of ASCS before and after the implementation of the health transformation plan (HTP) in Iran. METHODS: This research was a before–after quasi-experimental study. The study population included all patients hospitalized in the largest general hospital of Kurdistan province with five diseases such as asthma, diabetes, hypertension, congestive heart failure, and chronic obstructive pulmonary disease in 2014 (before the implementation of the HTP) and 2015 (after the implementation of the HTP). Data were analyzed by SPSS v.20 using Chi-square test. FINDINGS: Total number of hospitalizations before and after the implementation of the HTP was 1501 and 1405, respectively. Moreover, the proportion of PHs in all types of the hospital admissions before and after the implementation of the HTP was 47% and 49%, respectively. There was no statistically significant difference between the number of PHs before and after the HTP. In total, PHs imposed 885 798 US$ and 9920 bed-days on health system before and after the implementation of the HTP. CONCLUSION: Despite the previous expectations of policy makers for improving quality, efficiency, and access to primary health care through implementation of the HTP, proportion of PHs is considerable and it imposes a lot of costs and bed-days on the health system both before and after the HTP.